Effect of planting substrate based on Yellow River sediment for ecological restoration in mining area - Liang SONG; Bingqin ZHAO; Dong XIA; Xin WU; Xinkai HU; Wennian XU; Hailong BAO (Meitan kexue jishu)
The primary constraint for the ecological restoration of mining areas in the Yellow River basin is the significant scarcity of topsoil resources. The predominant loss of soil particles in the form of Yellow River sediment holds crucial value for utilization purposes. Natural soil was substituted for Yellow River sediment in this study, and Portland cement was employed as the binder. Planting substrates were prepared by adding various amounts of cement, broken corn stalks, and various external materials. Orthogonal testing was performed in situ at the landfill slope of the Suhaitu mining region in Wuhai City. The ecological restoration effect of the planting substrate based on Yellow River sediment was evaluated by monitoring the moisture and strength characteristics of the planting substrate and the plant's physiological characteristics. The results showed that cement as a hard material can improve the planting substrate strength compared with CK treatment, and the increased range was 0.62−1.67 times. However, 6% high cement content made the planting substrate dry and shrink, reduced the internal friction angle 1.2°−4.1°, and had an inhibiting effect on the germination stage of the plant. The sediment in the Yellow River is silty sand with few pores. The organic material can significantly improve the pore structure of the planting substrate, and increase the maximum water storage capacity of the substrate by 12.57%−15.88%. In addition, the soil water infiltration rate was increased by 35.56%, which was beneficial to the growth and development of plant roots. In addition, fibrous straw can improve the ductility of the planting substrate to a certain extent and inhibit the extension and expansion of substrate cracks. When the amount of cement and organic materials were both 4%, the cohesion of the planting substrate reached a peak of 25.17 kPa. Correlation analysis and PLS–PM comprehensive analysis showed that under the combined effect of plant physiological characteristics, except for plant height, the variance of other indicators was greater than 0.7. The overall planting state can meet the slope ecological restoration requirements, and the plants were in a relatively stable growth state in the later stage. In conclusion, when the content of cement and organic materials is 4%, the water-retaining and strength characteristic of the Yellow River sediment-based planting substrate can achieve optimization, and is suitable for ecological restoration and plant growth in abandoned mining areas with a shortage of water and soil resources. This research can be extended to other lakes and reservoirs involving dredging in the Yellow River Basin, which can play an important role in the ecological conservation and restoration of the Yellow River Basin and has a wide application perspective.